Compositional changes of selected amino acids, organic acids, and soluble sugars in the xylem sap of N, P, or K‐deficient tomato plants. Issue 5 (20th August 2015) - Sung, Jwakyung; Sonn, Yeonkyu; Lee, Yejin; Kang, Seongsoo; Ha, Sangkeun; Krishnan, Hari B.; Oh, Taek‐Keun
Abstract Xylem sap plays a major role in long‐distance transport of water, nutrients, and metabolites. However, there is little information on the behavior of metabolites in mineral‐deficient xylem sap. For this reason, the time‐dependent changes in selected metabolites (amino acids, organic acids, and soluble sugars) from tomato xylem sap in response to nitrogen (N), phosphorus (P), or potassium (K)‐deficient condition were investigated. Tomato plants (Solanum lycopersicum L.) were grown hydroponically in liquid culture under three different mineral regimes: N‐deficient [0.5 mM Ca(NO3)2 and 0.5 mM KNO3], P‐deficient (0.05 mM KH2PO4), and K‐deficient (0.5 mM KNO3), respectively. Xylem sap was collected at 10:00 am after 1, 5, 15, and 30 d, and the selected metabolites were analyzed with liquid chromatography. All N, P, or K deficiencies led to a substantial increase in metabolites in the xylem sap. The predominant amino acid in the xylem sap was glutamine and, interestingly, all mineral deficiencies resulted in a substantial amount of γ‐aminobutyric acid (GABA). Additionally, organic acids (citrate and malate) and soluble sugars were strongly increased in all mineral deficiencies, and, in particular, the level of shikimate was greatly affected by N deficiency. Based on these data, it is necessary to clearly elucidate an unknown event taking place in xylem loading in a variety of environmental impacts, and we are now studying to expand our knowledge on metabolic and proteomic responses using GC‐MS and LC‐MS.